Entrepreneurial Intentions of Vocational Education Students in Indonesia: PLS-SEM Approach - Fawaid, Moh; Triyono, Mochamad Bruri; Sofyan, Herminarto; Jatmoko, Dwi; Abdul Majid, Nuur Wachid; Rabiman, Rabiman (Journal of Technical Education and Training, 2022)
Cultivating entrepreneurial intentions in vocational education students is important in preparing graduates ready for entrepreneurship. However, efforts to foster entrepreneurial intentions are still a serious problem in vocational education. This study examines the structural model of the influence of entrepreneurial interest, technological competence, digital marketing, internship experience, self-efficacy, and entrepreneurial personality on entrepreneurial intentions. Ex-post facto research with a structural approach involving 618 vocational education students in Indonesia. Data was collected through a closed questionnaire with a Likert scale of 1-4 distributed using Google Form media. The collected data were analyzed using structural equation model analysis with path analysis and bootstrap methods. The study results show that technological competence, digital marketing, and apprenticeship experiences significantly affect the growth of entrepreneurial intentions. In addition, self-efficacy and entrepreneurial personality also significantly succeeded in mediating the influence of technological competence, digital marketing, and internship experience on entrepreneurial intentions. Teachers as learning facilitators must foster an interest in entrepreneurship as the basic root of the spur to form aspects of competence and experience needed in the business world. This aspect must also be given and strengthened to form a personality in entrepreneurship and strengthen self-efficacy so that the estuary of entrepreneurial intentions inherent in students will be stronger. This research is limited to certain variables based on the current actual theory. Future research needs to examine more deeply the potential influence of other variables that are more effective in growing students’ entrepreneurial intentions in vocational education.